2021
DOI: 10.1111/papt.12362
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences of therapy for borderline personality disorder: Commonalities and differences between dialectical behaviour therapy and mentalization‐based therapy and relation to outcomes

Abstract: Objectives Dialectical behaviour therapy (DBT) and mentalization‐based therapy (MBT) are widely used evidence‐based psychological treatments for borderline personality disorder (BPD). The study aimed to establish evidence on common and unique, and helpful and unhelpful, treatment processes. Design Mixed‐methods. Methods In‐depth qualitative interview data on patient experiences during treatment were combined with quantitative outcome measures in 73 patients diagnosed with a personality disorder and receiving D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…Engagement with the programme was encouraging, in that only 21% of participants dropped out, coupled with an 85% session attendance rate that was consistent across the duration of therapy. It is possible that the attendance level positively correlates with the sustained outcome data and specific attention to the cultivation of safeness in the therapeutic process in CFGP which has been cited as a missing component in other therapies (Barnicot et al, 2022). This attrition rate was lower than that of published literature reviews of treatments for people with a diagnosis of personality disorder which indicated 37% non-completion rate (Arntz et al, 2023;Hummelen et al, 2007;McMurran & Ward, 2010).…”
Section: Discussionmentioning
confidence: 87%
“…Engagement with the programme was encouraging, in that only 21% of participants dropped out, coupled with an 85% session attendance rate that was consistent across the duration of therapy. It is possible that the attendance level positively correlates with the sustained outcome data and specific attention to the cultivation of safeness in the therapeutic process in CFGP which has been cited as a missing component in other therapies (Barnicot et al, 2022). This attrition rate was lower than that of published literature reviews of treatments for people with a diagnosis of personality disorder which indicated 37% non-completion rate (Arntz et al, 2023;Hummelen et al, 2007;McMurran & Ward, 2010).…”
Section: Discussionmentioning
confidence: 87%
“…A mixed-methods re-analysis of the previously mentioned non-randomized comparison of DBT and MBT 61 found that patients’ accounts of learning not to react impulsively, questioning one’s thoughts and assumptions, communicating more effectively, and exposing oneself to painful emotions were associated with less self-harm at the end of treatment across both therapies. 62 Also, difficulties in the therapeutic relationship or with group members were associated with more severe BPD severity and emotion dysregulation at end of treatment for both MBT and DBT. 61 , 62 …”
Section: Dbt and Mbt: Two Of A Kind?mentioning
confidence: 95%
“… 62 Also, difficulties in the therapeutic relationship or with group members were associated with more severe BPD severity and emotion dysregulation at end of treatment for both MBT and DBT. 61 , 62 …”
Section: Dbt and Mbt: Two Of A Kind?mentioning
confidence: 95%
“…Over the past decade, the use of qualitative methods to investigate patient experiences of psychotherapy for BPD is accumulating, with a significant number of studies focusing on DBT (10,11). To the best of our knowledge, four qualitative papers and one mixed-method paper focusing on patient experiences of MBT, primarily long-term, for BPD has been published (12)(13)(14)(15)(16). Lonargáin et al (15) explored seven outpatients' experiences with MBT for BPD (duration ranging from 3 to 14 months).…”
Section: Introductionmentioning
confidence: 99%
“…Even though patients perceived MBT as helpful, the patients did not feel like they were cured ( 14 ). In a mixed-method study, Barnicot et al ( 12 ) interviewed 73 outpatients with a personality disorder, primarily BPD, who attended either DBT (duration: 12 months) or MBT (duration: 18 months) ( 13 ). The study pointed to helpful and hindering common factors across DBT and MBT for BPD, but also elements unique to the different models.…”
Section: Introductionmentioning
confidence: 99%